Developing the third world : the experience of the nineteen-sixties - Robinson, Ronald Edward (Cambridge : University Press, 1971)
This is a selection of papers from the Cambridge conferences on development in third world during the 1960s.
Includes bibliographies.
lje 1/08/18
Loans
Keywords: Economic development; Economic conditions; Economic assistance; Pakistan; India; South America